FAKTOR-FAKTOR PENENTU KINERJA KEUANGAN USAHA AYAM BROILER DI KOTA KENDARI - Normal Bivariant Padangaran; Dwi Rachmina; Anna Fariyanti (Forum Agribisnis, 2017)
Financial performance is one of measure to determine the condition of a business. The objectives of this research are: (1) to analyze the financial performance of broiler business in Kendari City; and (2) to analyze determinant factors of financial performance of broiler business in Kendari City. Research method uses financial ratio analysis and path analysis. The research was conducted in Kendari City with 72 respondents. The results of the research showed that: (1) number of chickens average 3.849 tails, were managed by partnership method and 8 times production in a year; (2) financial performance of broiler business are profitable; (3) number of production positive influenced by number of Day Old Chicken (DOC), number of labor, wide of cage, and experience on farming ; (4) the influence factor of current ratio, total assets turn over ratio, and profitability are number of production, equity ratio, and experience on farming. Based on the research results, then recomendate to: (1) farmers need to increase the production capacity of each production cycle or expanding businesses to use assets more efficiently and the income generated is also greater; (2) therefore the financial performance of broiler business was positively affected by the number of production, equity ratio, and experience on farming, to be able to increase operating profit and financial performance of the business it is suggested that these three things improved.